2017
DOI: 10.1007/s00737-017-0762-5
|View full text |Cite
|
Sign up to set email alerts
|

The association of experience of violence and somatization, depression, and alexithymia: a sample of women with medically unexplained symptoms in Turkey

Abstract: The aim of the study was to examine the relationship between the levels of somatization, depression as well as alexithymia, and MUS in women going through violence experience in three contexts (childhood, adulthood, and both childhood and adulthood). The study was performed on 180 patients attending the Internal Medicine Department of Istanbul University Medical Faculty. The data of women with MUS (n = 50) were compared those of women with acute physical conditions (n = 46) and chronic physical conditions (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
1
10
0
1
Order By: Relevance
“…Previous research has also identified a link between childhood abuse experiences and HA (Anuk and Bahadir, 2018; Bailer et al, 2014; Barsky et al, 1994; Brown et al, 2005; Fiddler et al, 2004; Haugaard, 2004; Reiser et al, 2014; Salmon and Calderbank, 1996; Taycan et al, 2014; Weck et al, 2014). Specifically, relationships have been found between childhood sexual and physical abuse and two components of HA (i.e.…”
mentioning
confidence: 95%
“…Previous research has also identified a link between childhood abuse experiences and HA (Anuk and Bahadir, 2018; Bailer et al, 2014; Barsky et al, 1994; Brown et al, 2005; Fiddler et al, 2004; Haugaard, 2004; Reiser et al, 2014; Salmon and Calderbank, 1996; Taycan et al, 2014; Weck et al, 2014). Specifically, relationships have been found between childhood sexual and physical abuse and two components of HA (i.e.…”
mentioning
confidence: 95%
“…Another study by Dilek et al on depression symptoms was conducted using semistructured interviews. The results of the study indicated that signs of somatization, aggression, and violence were common symptoms of depression (Anuk & Bahadır, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Only the differences for the working and economic status were significant between the groups. There are studies in the literature reporting that there were associations between somatization and anxiety and that individuals with a low educational status had higher somatization and anxiety levels (4,5). In addition, it was reported that anxiety level was higher and the threshold for tolerating the anxiety was lower in female gender (4).…”
Section: Discussionmentioning
confidence: 99%
“…Across different cultures throughout the world, physical symptoms are the most common form for an individual to express emotional distress and social problems (5). One of the somatic symptoms that are difficult to explain medically is common musculoskeletal pain (6).…”
Section: Introductionmentioning
confidence: 99%